(untitled) (Bangladesh Medical Journal Khulna, 2017)
Background: A pleural effusion represents the disruption of the normal mechanisms of formation and drainage of fluid from the pleural space. Pleural effusions are associated with diseases of varied etiologies and often carry a grave prognosis. Objective: To evaluate the common cause of pleural effusion in developing country and also to compare to that of developed countries. Methods: This is a prospective observational study. Fifty four patients, diagnosed with pleural effusion on admission were randomly selected from I April 2016 to 30 September 2016 in Medicine ward of Khulna medical college hospital. Etiologic diagnosis was established by sequential clinical history and findings on physical examination, laboratory tests, chest radiograph, CT Scan of chest and pleural fluid analysis. Patients who remained undiagnosed were subjected to fibre-optic bronchoscopy, thoracoscopic pleural biopsy, and histopathology. Results : Etiologic diagnosis of pleural effusion was established in 50 (92.59%); tuberculosis 25 (46.29%), parapneumonia 10 (18.52%) malignancy 7 (12.96%) nephrotic syndrome 3 (5.55%),cirrhosis of liver disease 2 (3.71%) congestive cardiac failure 2 (3.71%), systemic lupus erythematosus I (1.85%). 4 patients (7.41%) remain undiagnosed. Among subjects, exudative pleural effusion was 43 (79.63%) and transudative 11 (21 57%). Among exudative pleural effusion sputum for AFB positive 15 (34.88%), FNAC 10 (23%), fibreoptic bronchoscopy was positive 2 (4.6%), gene expart test for tuberculosis positive in 5 (11.62%). Conclusions: Most of the pleural effusion cases are diagnosed as tuberculosis, Early and adequate treatment results in complete recovery of the patient. Bang Med J (Khulna) 2016; 49 : 27-30